The care tasks in Rome. Looks inside the family (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
This article analyzes the Rome film of the Mexican director Alfonso Cuarón. The study focuses on the care experiences developed within the family, whose protagonist is a domestic employee. We consider that the cinema constitutes a powerful tool for the questioning of the obvious, the production of questions where there are none, and the creation of new spaces of interpellation of reality. In this sense, our work aims to be a gender-based contribution that addresses the resignification of the language used to designate the issues and problems that affect women.
Keywords: Care; domestic work; private space; gender; cinema